The Effect of Loyalty Program and Service Quality on Customer Loyalty in Telecommunications Services PT PLN Icon Plus - Huda, Miftahul; Supriyono, Supriyono (Formosa Journal of Science and Technology, 2024)
The increase in people's need for access to information to connect with the outside world has triggered an increase in demand for telecommunications services, this has led to the relatively rapid growth of the digital telecommunications industry in Indonesia. This research aims to determine the impact of loyalty programs and service quality on customer loyalty. The research method used is a quantitative method using PLS in analyzing the results. There were 100 people as samples in this research obtained using a purposive sampling technique. This data was collected by distributing questionnaires to respondents via Google Form. The results of this research show that loyalty programs and service quality have a significant positive effect on customer loyalty in PT PLN ICON PLUS telecommunications services.